HOW THE PERCEPTION AND LIFE STYLE OF SMALL SCALE MINERS EFFECT THE GREEN BUSINESS SUSTAINABILITY IN TEWANG PAJANGAN VILLAGE OF CENTRAL KALIMANTAN - Yuli Sintha Asi, (Journal of Innovation Research and Knowledge, 2025)
The aim of this research is to describe the effect of perception and life style of small scale miners towards their continuity of livelihood in Tewang Pajangan Village of Central Kalimantan. It is a descriptive quantitative. The respondents of the research is the total number of population. The findings of the research are (1). Perception does not have significant effect on green business sustainability with a significance level of 0.223 > 0.05 . (2). Life style has significant effect on green business sustainability with a significance level of. 0.027 < 0.05. The difficulty of officially detecting the names of miners makes it difficult to demand accountability. The report and mutual coordination and socialization among the officers related to green sustainability business are suggested. The culture of shifting cultivation of local people in the past is not accordance with the ongoing green business sustainability